Area equivalents for spinning reserve determination in interconnected power systems. (August 2015) - Shayesteh, E.; Amelin, M.; Soder, L.
Abstract: The current study applies the cost-benefit analysis method to determine the optimal amount of spinning reserve. However, it is difficult for the method to handle large size problem, like large interconnected power systems with several control areas, directly. Therefore, this paper proposes a power system equivalent for the original system to reduce the complexity of the original problem. According to the proposed algorithm, each area of the system is first modeled by an equivalent system, obtained by the REI (radial – equivalent – independent) method, and an interconnected REI equivalent is obtained for the original interconnected system. A cost-benefit analysis is then performed to determine the spinning reserve requirements of both the original and equivalent systems. The cost-benefit algorithm considers either the SCUC (security constrained unit commitment) or the SCED (security constrained economic dispatch). Finally, the proposed interconnected REI equivalent is evaluated by comparing the spinning reserve of each control area in the original system with that in the equivalent system. Numerical studies are performed on two IEEE test systems. Highlights: Spinning reserve calculation by cost-benefit method may need high computational time. One solution is to make an equivalent and calculate the reserve for the small system. An interconnected REI equivalent is obtained for the original system in this paper. Obtained reserve in equivalent system can accurately estimate the original reserve. Making the equivalent system and obtaining the reserve for it need much less time.